Data-Driven Marketing Strategy: The Role Of Big Data And Business Intelligence At Pt Pertamina Retail Fuel Marketing - John Sihotang; R.A. Aryanti Wardaya Puspokusumo; Imas Komariyah; Mohamad Abduh Alfahlepi (JAKI : Jurnal Akuntansi, 2025)
Personal and public data have become essential elements in modern business operations. The digitalization of information allows data to be used as a foundation for decision-making, particularly in business development. When properly utilized, collected data can inform strategic decisions across various functions, including marketing. Widely dispersed data can be transformed into valuable insights through the analysis of raw information (big data). Moreover, the application of business intelligence (BI) enhances these insights, converting them into strategic knowledge that organizations can apply effectively across business development areas. This study focuses on three key variables: the independent variable (big data), the dependent variable (marketing strategy development), and the moderating variable (business intelligence). In the fuel retail industry, marketing strategy development requires a comprehensive analysis of big data and business intelligence. Companies must prioritize personal data (customer information), public data (societal sentiment), and internal data to develop effective marketing strategies. The integration of big data as a foundational information source, combined with BI analysis, is shown to enhance the effectiveness of marketing strategy development. This research demonstrates that big data significantly influences marketing strategy formulation. Additionally, when business intelligence is effectively implemented alongside big data, it amplifies this impact. Organizations in the fuel retail sector are especially reliant on consumer preferences and public sentiment, making the development of robust big data and BI analytics systems crucial for strategic marketing success.